DISINFECTANT APPLICATION LEVELS IN COWSHED FOR PREVENTING OF FOOT AND MOUTH DISEASES IN GIANYAR - Ni Ketut Vonny; I Ketut Suada; I Wayan Masa Tenaya (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Foot and mouth disease (FMD) is a contagious viral disease that attacks cloven-hoofed livestock such as cattle, buffalo, sheep and goats. The spread of FMD in cattle is prone to occur, therefore efforts are needed to prevent transmission and spread of the disease, one of which is through biosecurity management, namely sanitation and disinfection. The aim of this research is to determine the level of implementation of disinfection in cattle pens and its relationship to preventing FMD cases in cattle in Gianyar Regency, Bali. The data collection method used a questionnaire by conducting interviews with one member of each cattle breeder group consisting of simantri and non-simantri breeder groups in Gianyar Regency. The results of this study show that the level of application of disinfection in preventing FMD by cattle breeders in Gianyar Regency is classified as poor (score ≤ 60%) by 76.7% of breeders, is classified as sufficient (score 60-75%) by 23.3% of breeders, and is classified as good (score ≥ 76%) as many as 0% of breeders. Meanwhile, no relationship was found between the level of disinfectant application and the prevention of FMD cases. It was concluded that cattle breeders in Gianyar Regency had a poor level of disinfection implementation and prevention of FMD transmission had been carried out through vaccination which had an effect on reducing cases. However, implementing disinfection is also important to prevent the possibility of livestock being infected by other infectious diseases. Therefore, breeders are expected to implement biosecurity, namely continuous disinfection to prevent the possibility of infection from other diseases on the farm.